2013
DOI: 10.1159/000349927
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Erythrocytosis in Dialysis Patients: A Case Report and Literature Review

Abstract: Anemia is a common complication in end-stage renal disease (ESRD) patients. On the other hand, idiopathic erythrocytosis is extremely rare, with only a few cases reported in the literature. We present a case of erythrocytosis that developed after initiating hemodialysis. A 68-year-old male with a history of ESRD secondary to diabetes presented with erythrocytosis that started a few months after initiating dialysis in the absence of having received erythropoietin-stimulating agents or iron supplements. His eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Sheqwara et al [8] reported occurrence of idiopathic erythrocytosis in a hemodialysis patient. The differences from our patient were as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheqwara et al [8] reported occurrence of idiopathic erythrocytosis in a hemodialysis patient. The differences from our patient were as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired renal cystic disease is a frequently reported cause of secondary erythrocytosis in hemodialysis patients. The main mechanism of elevation in the serum erythropoietin levels in patients with acquired renal cystic disease involves the overproduction of erythropoietin by the epithelial lining of renal cysts [8] .…”
Section: Discussionmentioning
confidence: 99%
“…2 Pada umumnya pasien diberikan terapi ESA bila kadar hemoglobin di bawah 10g/dl karena keadaan anemia kronik sangat berbahaya bagi pasien PGK. 3 Pada beberapa kondisi ditemukan kadar hemoglobin yang normal pada pasien PGK yang menjalani terapi dialisis dengan status kadar hormon eritropoietin yang normal walaupun tanpa pemberian terapi ESA sebelumnya. Kondisi tersebut dapat ditemukan antara lain pada pasien PGK dengan koinfeksi hepatitis C. 3,4 Kami melaporkan sebuah kasus seorang laki-laki berusia 61 tahun dengan PGK dan ko-infeksi hepatitis C yang menjalani terapi hemodialisis di RSUP Prof. Dr. Dr. R. D. Kandou Manado.…”
Section: Pendahuluanunclassified
“…Eritropoietin umumnya dibentuk dari ginjal, tetapi hati juga dapat memroduksi eritropoietin dalam jumlah kecil. 3 Pasien yang rutin menjalani hemodialisis sering dikaitkan dengan infeksi hepatitis C mengingat proses penularan infeksi hepatitis C ialah dengan penetrasi langsung virus tersebut ke dalam membran sel dan menyebar ke sel darah. Pada pasien PGK yang harus menjalani hemodialisis secara rutin akan berisiko terinfeksi heaptitis C lebih tinggi.…”
Section: Bahasanunclassified
“…However, in many instances, the mechanism of erythrocytosis in ESRD patients is unknown. Renal EPO production is stimulated by decreased oxygen carrying capacity (hemoglobin concentration x O 2 saturation x cardiac output) [16]. Because the ability to secrete EPO is diminished in chronic kidney diseases, most ESRD patients require erythropoiesis-stimulating agents (ESA) to prevent anemia [7].…”
Section: Introductionmentioning
confidence: 99%